Quantitative Proteomics and Transcriptomics Reveals Differences in Proteins During Anthers Development in Oryza longistaminata - Sun, Yue; Wang, Xin; Chen, Zhongkai; Qin, Lu; Li, Bai; Ouyang, Linjuan; Peng, Xiaosong; He, Haohua (Frontiers in Plant Science, 2021)
Oryza longistaminata is an African wild rice species that possesses special traits for breeding applications. Self-incompatibility is the main cause of sterility in O. longistaminata, but here we demonstrated that its pollen vitality are normal. Lipid and carbohydrate metabolism were active throughout pollen development. In this study, we used I2-KI staining and TTC staining to investigate pollen viability. Aniline-blue stained semithin sections were used to investigate important stages of pollen development. Tandem mass tags (TMT)-based quantitative analysis was used to investigate the profiles of proteins related to lipid and carbohydrate metabolism in 4-, 6- and 8.5-mm O. longistaminata spikelets before flowering. Pollen was found to germinate normally in vitro and in vivo. We documented cytological changes throughout important stages of anther development, including changes in reproductive cells as they formed mature pollen grains through meiosis and mitosis. A total of 31 987 RNA transcripts and 8753 proteins were identified, and 6842 of the proteins could be quantified. RNA-seq and proteome association analysis indicated that fatty acids were converted to sucrose after the 6-mm spikelet stage, based on the abundance of most key enzymes of the glyoxylate cycle and gluconeogenesis. The abundance of proteins involved in pollen energy metabolism was further confirmed by combining quantitative real-time PCR with parallel reaction monitoring (PRM) analyses. In conclusion, our study provides novel insights into the pollen viability of O. longistaminata at the proteome level, which can be used to improve the efficiency of male parent pollination in hybrid rice breeding applications.